Increased exposure to air pollutants leads to greater atherosclerotic burden mediated by systemic inflammation. (25th November 2020) - Theofilis, P; Oikonomou, E; Vogiatzi, G; Lazaros, G; Mystakidi, V.C; Barbaresos, N; Tasios, P; Tsalamandris, S; Fountoulakis, P; Miliou, A; Papaioannou, N; Asimakopoulos, M.N; et al.
Abstract: Introduction: Air pollution has been a well-described environmental factor contributing significantly to the global disease burden. Purpose: To examine the association of gaseous air pollutants with atherosclerosis, especially in subjects with coronary artery disease (CAD). Methods: 2053 individuals enrolled in the Corinthia study underwent clinical and biochemical assessment followed by carotid ultrasonography to evaluate carotid intima-media thickness (cIMT) and plaque burden. Inflammation was estimated via measurement of C-Reactive protein (CRP). Air pollutants concentration analysis was performed in prespecified regions with respect to their proximity to heavy industries, highways and shipyards. Results: A higher concentration of gaseous air pollutants was observed in Region 4 when compared to other regions (Table). Mean cIMT, maximum cIMT and carotid plaque burden were significantly increased in individuals of Region 4 (Table, Figure A and B), a result which remained unaffected after adjustment for cardiovascular confounders (Figure C). In parallel, inhabitants of Region 4 had higher levels of CRP (Region 1: 4.60±5.01mg/l; Region 2: 3.08±3.26mg/l; Region 3: 4.37±4.70mg/l, Region 4: 6.78±9.77mg/l, p<0.001). To examine the effect of air pollution on atherosclerosis in CAD, propensity scores were applied to match healthy controls with CAD subjects in terms of atherosclerosis risk factors resulting in two matched groups; one in regions 1, 2 and 3 -low air pollution areas (LAPA)- and another in region 4 -high air pollution area (HAPA). Interestingly, we noted substantially higher inter-area differences in mean cIMT of CAD individuals (Figure D). Conclusion: Air pollution may significantly contribute to atherosclerosis progression, potentially via the induction of inflammation. A more pronounced effect was noted in CAD individuals exposed to high air pollution. Funding Acknowledgement: Type of funding source: None